Exploring Risk Factors and Outcomes of Low-Birth-Weight Infants in the Misurata Medical Center NICU - A Retrospective Analysis (2022) - Elburki, Salima Mukhtar; Assadi, Moktar Ahmed; Agdawra, Faraj Ali; Assadi, Abdulaleem Ahmed; Rajab, Ali Abdulsalam (Journal of medical and pharmaceutical sciences, 2024)
Objective: To examine the characteristics and outcomes of low-birth-weight (LBW) newborns admitted to the NICU at Misurata Teaching Hospital in 2022, and to identify key factors influencing their survival. Patient’s and methods: a retrospective descriptive study included 199 LBW newborns (<2.5kg) admitted to the NICU during the study period. Data were collected from medical records and analyzed using descriptive statistics. Results: Maternal factors: Mothers aged 30-35 years had the highest mortality burden. Clear amniotic fluid was associated with the highest death rate, despite being the most common finding. Gestational age showed a clear inverse relationship with survival, with mortality reaching 100% for infants born before 28 weeks. Low APGAR scores were a significant predictor of mortality. RDS and sepsis were the most common diagnoses, with RDS having the highest mortality rate. Elective caesarean section had the lowest mortality rate, while normal vaginal delivery and urgent C-section had higher rates. Cephalic presentation, though most common, had a higher mortality rate than breech presentation. Conclusion: LBW newborns in Misurata Teaching Hospital faced a complex interplay of maternal, neonatal, and delivery-related factors influencing their survival. Further investigation into maternal factors and individualized delivery management is warranted to improve the prognosis of LBW newborns in this population.